The transition from amalgam to other restorative materials in the U.S. predoctoral pediatric dentistry clinics - Elham T. Kateeb; John J. Warren (Wiley, 2019)
Abstract Increased concerns about the safety of amalgam restorations in children have resulted in many dental schools emphasizing the teaching of alternative dental materials. This study investigated the current teaching of different dental materials for use in posterior teeth in the United States predoctoral pediatric dentistry programs. In 2011, the authors invited the chairs of the predoctoral pediatric dentistry departments in all accredited dental schools at that time (N = 57) to participate in an internet‐based survey. Descriptive statistics were calculated to describe the frequency of using different restorative materials. Regression models were developed to explore the factors related to the use of dental restorations in predoctoral pediatric clinics. Among the 44 dental schools that responded (77% response rate), 74% used amalgam, and 93% used composite in primary posterior teeth. Glass ionomer was used by 61% of the schools in primary posterior teeth. Placing amalgam in primary posterior teeth was associated with programs that treated more 3-5‐year‐old patients (β = .302, p < .043), whereas the use of glass ionomer was associated with having students serving at off‐site satellite dental clinics (β = .015, p < .012). In general, having departments with chairs who had positive attitudes towards Minimal Invasive Dentistry (MID) used composite (β = .091, p < .0001) and glass ionomer (β = 103, p < .0001) more frequently and were less likely to use amalgam (β = −.077, p < .005) in primary posterior teeth. Although teaching MID concepts in predoctoral pediatric clinics in dental schools is increasing, the use of amalgam in posterior primary and permanent teeth is still widely practiced.